Loan Portfolio Composition and Bank Risk: An Accounting-Based Evidence from Asia-Pacific Countries - Febrianti, Devi; Putri, Nyayu Khalilah; Oktarini, Kurnia Widya; Firza, Edy; Saputri, Ulfah Tika; Dwi Anugrah, Meilinda (LPPM Universitas Jambi, 2025)
This study aims to examine the effect of loan portfolio composition on bank risk in Asia-Pacific countries. From a banking accounting perspective, loan portfolio composition represents a key component of earning assets, reflecting asset quality, credit risk exposure, and the effectiveness of banks in managing income sources and risk. The relationship between loan portfolio composition and bank risk remains inconclusive in both theoretical and empirical literature. On the flip side, a more diversified loan portfolio may reduce risk through diversification benefits. On the other hand, increased diversification may also lead to higher complexity, potential moral hazard, and excessive risk-taking behavior. This study employs data from commercial banks across 15 Asia-Pacific countries over the period 2011–2022. Bank risk is measured using the Ln.Z-score, while loan portfolio composition is proxied by income diversification. The results indicate that loan portfolio composition has a negative effect on bank risk, suggesting that banks with more diversified loan portfolios tend to have lower risk and greater income stability. This study contributes to the banking accounting literature by highlighting that loan portfolio composition is not only an intermediation instrument but also an important indicator of asset quality, credit risk, and financial stability. The findings provide practical implications for regulators and bank management in strengthening risk measurement, reporting, and monitoring systems.